Studying colon cancer using intestinal organoid models for anticancer drug and gene functional analysis - Kashfi, Seyed Mohammad Hossein (2020)
Colorectal tumours demonstrate broad genetic and phenotypic heterogeneity in comparison to their matched normal tissue. To shed light into this diversity in depth, an advanced in-vitro 3D model capable of self-renewal, self-organisation and exhibit organ functionality is required. Self-renewal of the small intestine and colonic epithelium is mediated by the proliferation of stem cells and their progenitors in the crypt base. Recently, a long-term and stable 3D culture system maintaining basic crypt physiology known as organoid became available from both normal and matched-tumour tissues of the intestine. Organoids faithfully reproduce functional genetic, pharmacological and morphological alterations exist in their parental tissue. Patient-derived organoids (PDO) can be generated and expanded indefinitely in-vitro from a small biopsy sample of CRC patients (from both tumour and adjacent normal tissue), providing a promising platform for personalised medicine, drug discovery and targeted gene editing research studies. Therefore, in this study, we have initially adapted patient-derived organoids culture from 17 CRC patients in our laboratory and further investigated the phenotypical alteration of both tumour, and normal adjacent derived organoids. Based on our findings, tumour organoids displayed different phenotypical traits from one patient to another, highlighting their distinct molecular subtyping. The growth and morphological alterations of tumour organoids also significantly differed from normal derived organoids in culture.